The Autobiography of Miss Jane Pittman - Tyson, Cicely; Dysart, Richard; Helmond, Katherine; Gaines, Ernest J., 1933-; Korty, John (Prism Entertainment, 1986)
Presents the story of the long life of Miss Jane Pittman, who began her life as a slave in the South and who marched for her civil rights in the 20th century at the age of 110.